Coordinated Processing of 3′ Slipped (CAG)(n)/(CTG)(n) Hairpins by DNA Polymerases β and δ Preferentially Induces Repeat Expansions - Chan, Nelson L. S. (American Society for Biochemistry and Molecular Biology, 2013)
Expansion of CAG/CTG trinucleotide repeats causes certain familial neurological disorders. Hairpin formation in the nascent strand during DNA synthesis is considered a major path for CAG/CTG repeat expansion. However, the underlying mechanism is unclear. We show here that removal or retention of a nascent strand hairpin during DNA synthesis depends on hairpin structures and types of DNA polymerases. Polymerase (pol) δ alone removes the 3′-slipped hairpin using its 3′-5′ proofreading activity when the hairpin contains no immediate 3′ complementary sequences. However, in the presence of pol β, pol δ preferentially facilitates hairpin retention regardless of hairpin structures. In this reaction, pol β incorporates several nucleotides to the hairpin 3′-end, which serves as an effective primer for the continuous DNA synthesis by pol δ, thereby leading to hairpin retention and repeat expansion. These findings strongly suggest that coordinated processing of 3′-slipped (CAG)(n)/(CTG)(n) hairpins by polymerases δ and β on during DNA synthesis induces CAG/CTG repeat expansions.